Academic Senate Minutes 2021-05-06 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 10/17/13 approved. Chair Report. President Report. Vice Chair Report. Vice President for Administration and Finance Report. Revision to the Periodic Review of Temporary Faculty approved for the Senate agenda. Discussion of Faculty Retreat. CFA Report. EPC Report. FSAC Report. Professional Sales Certificate approved for the Consent Calendar. Associated Students Report. Ex Com Rep to the Sustainability Ex Com Report. Senate agenda approved.